Aplikasi Pemilihan Karyawan Terbaik pada PT. Ql Trimitra dengan Metode Analytical Hierarchy Process (AHP) - Hernawan; Faizah, NM; Karo, Panser Karo (Journal Innovations Computer Science, 2022)
The research objectives are to design a web-based application that can help make the best employee selection report process easy and fast, design an application that can calculate normalization to determine criteria and weights according to the analytical hierarchy process (AHP) method, and design an application that can manage data -Alternative data needed for the selection of the best employees. The stages of data collection in this study consisted of 3 (three) stages namely; observation, interview, and literature study. UML (Unified Modeling Language) is used as an approach for modeling while the Analytical Hierarchy Process (AHP) method is applied in the best employee assessment application. The results of this study can facilitate the selection of the best employees to be faster with accurate results by using the best employee selection application by implementing the Analytical Hierarchy Process (AHP) method using the PHP and MySQL programming languages.